PENYULUHAN PENGGUNAAN FLEXIBLE MEDIAL ARCH SUPPORT DALAM MENGURANGI DERAJAT Q ANGLE KNEE JOINT PADA PENDERITA FLATFOOT - Anggriani, Atika Febri; Utomo, Prasetyo Catur (Jurnal Indonesia Mengabdi, 2026)
Pes planus (flat foot) is a condition characterized by the loss of the medial longitudinal arch of the foot, which can alter lower extremity biomechanics, including an increased Q-angle of the knee joint that may lead to functional knee disorders. This problem is commonly found among individuals with sports activities; however, knowledge regarding the management using flexible medial arch support remains limited. In order to decrease the Q-angle of the knee joint, this community service program aimed to increase the knowledge and abilities of people with flat feet in the use of flexible medial arch support. An initial survey, instructional sessions on flat foot, Q-angle of the knee joint, and flexible medial arch support, practical training on the device's usage, monitoring, and program assessment were among the implementation strategies. Over the course of a year, the program was carried out in phases, including administrative planning, coordination, instruction, hands-on support, and final assessment. The results indicated an increase in participants’ knowledge regarding the use of flexible medial arch support and their ability to apply the device independently. Furthermore, this activity contributed to improving community understanding of the role of orthotics and prosthetics in managing lower extremity disorders. An additional output in the form of educational video documentation was also produced to support broader information dissemination to the community.